A new species of Anisentomon from Hainan, Southern China (Protura: Eosentomidae) - Xiong, Yan; Bu, Yun; Yin, Wen Ying (Zootaxa, 2008)
Anisentomon hainanense new species is described from Hainan Province, Southern China. This species is characterized by the presence of four anterior setae on urosternites IV–VII and six setae on urosternites IX–X, also by one pair of curved spines on urotergite X in the position of setae A1.The shapes of the paired spines on urotergites X or XI are compared for the five known species of this genus. An updated key to the Chinese species of Anisentomon is also presented.